Antimicrobial resistance and vaccines in Enterobacteriaceae including extraintestinal pathogenic Escherichia coli and Klebsiella pneumoniae - Adriana Cabrera; Emily Mason; Liam P. Mullins; Manish Sadarangani (npj Antimicrobials and Resistance)
Abstract Antimicrobial-resistant Enterobacteriaceae are increasingly a clinical challenge. In particular, extraintestinal pathogenic Escherichia coli and Klebsiella pneumoniae threaten public health. Vaccination presents a long-term strategy to reduce both drug-susceptible and resistant infections while maintaining current clinical therapies. The review aims to emphasize the need for vaccines targeting extraintestinal pathogenic E. coli and K. pneumoniae by providing an overview of disease burden, antimicrobial resistance, therapeutics, and vaccine development.